Basic electromagnetism - Cowan, Eugene W. (Academic Press, 1968)
Contents: Chapter1: The Motion of charged particles; Chapter 2: The Electromagnetic Field; Chapter 3: Maxwell's Equations; Chapter 4: Electroagnetic Potentials